THE PLACE OF THE POOR IN LAUDATO SÍ - Jeffrey Goh (Asian Horizons, 2015)
In Laudato Sí, Pope Francis issued a call for an “ecological conversion” at every level of human life so that the cry of the earth and of the Poor may be heard and remedied. Examining the thoughts of a Pope known for his ministry to the Poor, this brief paper explores the place of the Poor in his encyclical from three lenses — anthropological, ecclesial, and socio-political. From “nature” to “creation”, from a disposable culture to a culture of awe, and from a fiercely anthropocentric, indifferent, and technocratic mindset to a vision of connectedness of all things, it traces the arguments and the spirit underpinning Francis’ text, so that the Creator may be praised for the gifts of creation, and humanity may learn not to be takers, users and abusers but, mindful of the Poor, to be appreciative receivers, givers and carers.